2006
DOI: 10.1186/1742-5581-3-7
|View full text |Cite
|
Sign up to set email alerts
|

Three options for citation tracking: Google Scholar, Scopus and Web of Science

Abstract: Background: Researchers turn to citation tracking to find the most influential articles for a particular topic and to see how often their own published papers are cited. For years researchers looking for this type of information had only one resource to consult: the Web of Science from Thomson Scientific. In 2004 two competitors emerged -Scopus from Elsevier and Google Scholar from Google. The research reported here uses citation analysis in an observational study examining these three databases; comparing cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
421
1
30

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 614 publications
(467 citation statements)
references
References 22 publications
15
421
1
30
Order By: Relevance
“…Schroeder (2007), comparing the same two tools, gives a comprehensive overview of studies comparing Google Scholar and Web of Science. In a comparative study of Google Scholar, Scopus and Web of Science, Bakkalbasi et al (2006) conclude that each of these tools has strengths in specific disciplinary searches. A behavioural study comparing Metalib with Google Scholar (Nygren et al, 2006) shows how students' preference for convenience leads to Google Scholar being their first choice.…”
Section: Enriched Information Literacymentioning
confidence: 99%
“…Schroeder (2007), comparing the same two tools, gives a comprehensive overview of studies comparing Google Scholar and Web of Science. In a comparative study of Google Scholar, Scopus and Web of Science, Bakkalbasi et al (2006) conclude that each of these tools has strengths in specific disciplinary searches. A behavioural study comparing Metalib with Google Scholar (Nygren et al, 2006) shows how students' preference for convenience leads to Google Scholar being their first choice.…”
Section: Enriched Information Literacymentioning
confidence: 99%
“…In several case [14,17] in which, for example, the scientific productivity of an author is described by the number of publications, citations and H-index, it is important to understand their sources, because the same variables may take different values if they are obtained via Web of Science, Scopus, Google Scholar or other disciplinary databases. In literature, there are also some papers in which the journal coverages of the various fields of these databases are compared [2,16,35] . In the greater part of these cases, although exceptions are made for medical sciences and some hard sciences, none of these is thoroughly exhaustive or representative.…”
Section: Indexes and Metricsmentioning
confidence: 99%
“…These findings were corroborated by the results of Vaughan and Shaw (2008) for information science. Bakkalbasi, Bauer, Glover, and Wang (2006) compared citation counts for articles from 11 oncology journals and 11 condensed matter physics journals published in 1993 and 2003. They found that for oncology in 1993, Web of Science returned the highest average number of citations (45.3), Scopus returned the highest average number of citations for oncology in 2003 (8.9), and Web of Science returned the highest number of citations for condensed matter physics in 1993 and 2003 (22.5 and 3.9, respectively).…”
Section: Literature Reviewmentioning
confidence: 99%